1984
DOI: 10.1086/161839
|View full text |Cite
|
Sign up to set email alerts
|

Effective temperatures and luminosities of very hot O type subdwarfs

Abstract: We observed 12 very hot 0-type subdwarfs with the IUE-satellite in the low dispersion mode. We derived temperatures from the slopes of the UVcontinua and estimated distances from the col g r excesses. Most of them are hotter than 60,000 K, i.e. they are the hottest known subdwarfs. From their spectral appearance and location in a H.R.-diagram they form a rather i nhomogeneous group. Three of them turned out to be central stars or nearly central stars, and four are definitely near the white dwarf stage. The sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 10 publications
0
38
0
Order By: Relevance
“…KV Vel, the central star of PN DS 1, was discovered to be a variable by Drilling et al (1984), with a period of 8.5 h. Drilling (1985) showed this star to be a double-lined spectroscopic binary and determined the primary stellar temperature to be 77,000 ± 8000 K from the ratio of the integrated near to far-UV flux from an IUE spectrum (Schönberner & Drilling 1984). Kilkenny et al (1988) presented a light curve in the U, B, V , and I bands, which confirmed the amplitude of 0.6 mag.…”
Section: A23 Dsmentioning
confidence: 99%
See 2 more Smart Citations
“…KV Vel, the central star of PN DS 1, was discovered to be a variable by Drilling et al (1984), with a period of 8.5 h. Drilling (1985) showed this star to be a double-lined spectroscopic binary and determined the primary stellar temperature to be 77,000 ± 8000 K from the ratio of the integrated near to far-UV flux from an IUE spectrum (Schönberner & Drilling 1984). Kilkenny et al (1988) presented a light curve in the U, B, V , and I bands, which confirmed the amplitude of 0.6 mag.…”
Section: A23 Dsmentioning
confidence: 99%
“…Walton et al (1993) reported no B − V color change with the orbital phase, which would indicate that the irradiated side of the companion is very hot. Indeed, the analysis of Pollacco & Bell (1993) determined a temperature on the bright side of the secondary of ∼25,000 K. They also deduced that the primary effective temperature is T eff ∼125,000 K from the ratio of integrated far-and near-UV light (Schönberner & Drilling 1984) and that the polar temperature is 115,500 K. This estimate is higher than was previously published (35,000-45,000 K; Bond et al 1978;Walton et al 1993), but it appears to be the best value to adopt in the absence of a full spectral fitting.…”
Section: A12 a 46mentioning
confidence: 99%
See 1 more Smart Citation
“…This further indicates that the spectral type of HD 145718 is A5Ve. Schönberner & Drilling (1984) suggested that HD 320156 (=LSS 4300) is a close binary system consisting of a helium supergiant of ∼1 M and a less luminous secondary. Our FEROS spectrum is compatible with this hypothesis.…”
Section: Hd 145718mentioning
confidence: 99%
“…To determine the temperature of the subdwarf companion, Kaler (1983) computed the Zanstra temperatures using the H and He ii nebular lines and constrained the primary component's temperature in between 32 000 and 60 000 K. In a most recent study, PB94 presented a new Zanstra analysis based on the Hβ and He ii nebular lines and estimated the temperatures as 48 000 and 82 000 K, respectively. They also employed the R‐technique of Schönberner & Drilling (1984) and derived a temperature of 63 000 ± 12 000 K for the primary star and considering the temperature range found from several methods they decided to adopt a temperature of 60 000 ± 10 000 K in the light‐curve analysis. However, the simultaneous two‐colour photometry gives us an opportunity to derive more accurate and approximate values for the temperatures of the binary components, which we have found as 49 500 K (fixed) for the primary and 3874 ± 120 K for the secondary star.…”
Section: Simultaneous Light‐curve Solutionsmentioning
confidence: 99%